Ketahanan Beberapa Varietas Padi terhadap Cercospora oryzae - Natya Lakshita; Susilo Hambeg Poromarto; Hadiwiyono Hadiwiyono (Agrotechnology Research Journal, 2019)
Rice is the source of staple food for most Indonesian people. The demand is continually increasing as the impact of increasing the people population. Sustainable development of rice must be done by the government. One of the problems in rice production is narrow brown leaf spot disease caused by Cercospora oryzae. This study aimed to determine the resistance of some varieties of rice to C. oryzae. The study was conducted on a field scale with natural inoculation and greenhouse with artificial inoculation using C. oryzae conidia suspension density of 105 conidia ml-1. The parameters observed, were incidence of disease, disease severity, the rate of infection, Area Under the Disease Progress Curve (AUDPC), and crops production. The result showed in the field that rice varieties of Gagak Hitam and Pandan Wangi were categorized as moderat resistant, while IR64, Inpari4, Sunggal and Ciherang showed high susceptible to C. oryzae. The results of greenhouse study showed that Hitam Gagak and Pandan Wangi rice varieties were categorized as resistant and IR64, Inpari4, Sunggal, Ciherang were moderate resistant (RR) against C. oryzae. The resistance of rice varieties affected by the interaction between pathogen genes that determine virulence and host genes that determine the resistance of the host plant.